Rice grading using image processing - Tahir, Wan Putri; Hussin, Norhaida; Htike@Muhammad Yusof, Zaw Zaw; Nyein Naing, Wai Yan (2015)
This paper focusing about the methods used for rice grading using image processing. Various approaches have been applied by previous researchers to solve different types of difficulties in grading the quality of rice. Machine vision has been used in most application of rice grader to differentiate rice grade based on special features such as shape, length, chalkiness, color and internal damage of rice. RGB color model, histogram, edge detection are some ways which have been used to differentiate and analyzed degree level of rice. In this paper, we are also discussing and suggesting another method in rice grading for Malaysia’s type of rice using image processing method based on several features which is length, colour and shape.